Gestão de risco no transporte rodoviário de produtos perigosos – Classe 1(explosivos) - Lopes, Carlos Alberto (2019)
Hazardous products transported by highways are a topic of great importance since the risks are related to the danger inherent in the transportation of this type of goods. Hazardous products are those that pose risks to the environment or to society, i.e., products that are toxic, flammable, corrosive, explosive, and that emit radiation and other chemicals, which represented a threat. This study aims to propose a directive for the risk management in the transportation of dangerous products of class 1, i.e., explosives, through the analysis conducted with specialists in the field, and based on legislation and research related to the transportation of dangerous products, from the perspective of risk management in order to offer the least risk during transport operations. The method used began with a bibliometric and systematic review to identify the criteria/risks, their mitigations and responses, and the data collection was performed through a structured interview. The result of this study identified the level of importance of the criteria/subcriteria regarding the transportation of explosives by road, the mitigation actions and the possible responses to minimize impacts. In the light of the research carried out, we verified that none of the publications in the literature exclusively addresses the criteria/risks used for transporting dangerous products, such as explosives. Besides, we believe that the proposal of this directive can serve as a guideline for risk management to contracting companies of carriers or companies that carry out this type of transport contributing to the improvement of its services.